(untitled) (Journal of Food and Dietetics Research, 2025)
Dietary diversity is a critical component of a healthy diet, essential for ensuring adequate nutrient intake and preventing diet-related diseases; however, women, particularly in low- and middle-income countries (LMICs), often face challenges in accessing diverse and nutrient-rich foods, leading to micronutrient deficiencies, exacerbated by socioeconomic fac tors, cultural environments, and food insecurity. This review aims to analyze the impact of dietary diversity and food security on women’s health, focusing on micronutrient adequacy among women of reproductive age (WRA) in LMICs, and explores effective methods for assessing dietary diversity and nutrient intake. The scope of this review includes studies conducted in LMICs, utilizing methodologies such as 24-hour dietary recalls and food frequency questionnaires to assess dietary diversity and nutrient adequacy. It examines the intake of key micronutrients like iron, zinc, calcium, and vitamins among WRA, and the implications of food insecurity on their nutritional status. Greater dietary diversity is associated with improved nutrient intake and overall health, especially for women of reproductive age. Addressing food insecurity and promoting nutrition-sensitive interventions are crucial for enhancing women’s health, supporting healthy pregnancies, and reducing maternal risks. Further research and interventions are needed to mitigate the disproportionate impact of poor dietary diversity and food insecurity on women’s well-being.